Demonstration of a ring‐FEL as an EUV lithography tool. (20th May 2020) - Lee, Jaeyu; Jang, G.; Kim, J.; Oh, B.; Kim, D.-E.; Lee, S.; Kim, J.-H.; Ko, J.; Min, C.; Shin, S.
Abstract : This paper demonstrates a ring‐FEL as an EUV lithography tool in a fourth‐generation storage ring. Abstract : This paper presents the required structure and function of a ring‐FEL as a radiation source for extreme ultraviolet radiation lithography (EUVL). A 100 m‐long straight section that conducts an extremely low emittance beam from a fourth‐generation storage ring can increase the average power at 13.5 nm wavelength to up to 1 kW without degrading the beam in the rest of the ring. Here, simulation results for a ring‐FEL as a EUVL source are described.